2018
DOI: 10.4143/crt.2017.346
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of the Number of Metastatic Lymph Nodes and a New Prognostic Scoring System for Recurrence in Early-Stage Cervical Cancer with High Risk Factors: A Multicenter Cohort Study (KROG 15-04)

Abstract: PurposeWe aimed to assess prognostic value of metastatic pelvic lymph node (mPLN) in early-stage cervical cancer treated with radical surgery followed by postoperative chemoradiotherapy. Also, we sought to define a high-risk group using prognosticators for recurrence.Materials and MethodsA multicenter retrospective study was conducted using the data from 13 Korean institutions from 2000 to 2010. A total of 249 IB-IIA patients with high-risk factors were included. We evaluated distant metastasis-free survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 29 publications
9
69
1
Order By: Relevance
“…Pathologic findings including positive resection margin, parametrial involvement, and lymph node metastasis are considered as high-risk factors for recurrence [28], and patients with these pathological features are believed to benefit from additional radiotherapy after radical hysterectomy [29,30]. Our results confirmed that the PFS and OS in patients with high-risk factors were significantly poorer than those without.…”
Section: Discussionsupporting
confidence: 77%
“…Pathologic findings including positive resection margin, parametrial involvement, and lymph node metastasis are considered as high-risk factors for recurrence [28], and patients with these pathological features are believed to benefit from additional radiotherapy after radical hysterectomy [29,30]. Our results confirmed that the PFS and OS in patients with high-risk factors were significantly poorer than those without.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study we observed that, in addition to the presence of positive nodes, the number of positive nodes had an impact on patient outcomes, thus adding new information useful for assessing patient prognosis. Other investigators observed similar results focusing on patients with suspected positive nodes at radiological examination 13–15. Wang et al conducted a retrospective study that included 114 patients undergoing radiotherapy (with or without chemotherapy) for cervical cancer.…”
Section: Discussionmentioning
confidence: 60%
“…Here, our investigation corroborated these findings, investigating the role of pathological positive nodes in a larger group of patients. Similarly, Kwon et al evaluated a group of 249 cervical cancer patients treated in 13 Korean institutions 14. They observed that the presence of multiple positive nodes (≥4) was an independent predictor for disease-free survival 14.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the number of metastatic pelvic lymph nodes (≤3 vs. >3) is a signi cant prognostic factor in patients treated with radical surgery followed by postoperative CCRT. Further, no signi cant survival difference is observed between patients without metastasis and those with 1-3 metastatic lymph nodes [20]. Park and Bae reported that the 5year OS rates for patients with stage IB-IIA cervical cancer and 0, 1, and ≥2 positive metastatic lymph nodes were 91, 80, and 47%, respectively (P = 0.006) [21].…”
Section: Discussionmentioning
confidence: 98%